Peran Administrasi Pertanahan dalam Perkembangan Wilayah Kota Tangerang Selatan - Ratna, Ni Luh Made Dwi; Mulyanto, Budi; Munibah, Khursatul (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2023)
South Tangerang City is experiencing a process of suburbanization, where the increase in population causes an increase in the need for space for development. If development activities are not controlled, it will reduce the quality of the environment and people's lives. Land management is an activity that aims to support development programs by utilizing the capacity of land resources. This study aims to analyze the level of regional development and analyze the influence of land administration in supporting regional development in South Tangerang City in 2016 and 2019. The level of regional development is analyzed weighted scalogram with modification of physical, social and economic variables. The relationship between the Y variable (Urban village development index-IPWK) and the X variable (Land administration) was modeled using Geographically Weighted Regression (GWR). The results of the regional hierarchy analysis show that the urban village in South Tangerang City are dominant in Hierarchy 3 with an average IPWK value result 46.25 (2016) and 45.38 (2019), as a hinterland for DKI Jakarta. Land administration activities can have different positive and negative effects locally on the level of development of the urban village area.